Retreatment Efficacy of Race Rotary Nickel Titanium system with or without Solvent in Oval Root Canals Obturated with Gutta Percha and Different Sealers (an invitro study ) - Haidy Samy William (2012)
Arabic Summary .
references (125-136).
Master Degree in Endodontics
faculty of Oral and Dental Medicine : Cairo University .
Keywords: Endodontics